Visualizing Lithium Dendrite Formation within Solid-State Electrolytes - Sun, Minghao; Liu, Tiefeng; Yuan, Yifei; Ling, Min; Xu, Nan; Liu, Yanyan; Yan, Lijing; Li, Hui; Liu, Chengyong; Lu, Yingying; Shi, Yao; He, Yi; et al. (ACS energy letters, 2021)
Solid-state electrolyte (SSE) is promising for application in all-solid-state lithium metal batteries because of its reliable safety and longevity. The failure of SSE to suppress dendrite formation of Li metal anodes has been conventionally explained by uneven Li deposition at Li/SSE interfaces and its subsequent dendritic growth. While Li deposition within SSE has been recently proposed as another key cause for SSE failure, little is known regarding the Li growth details inside the SSE itself. In this work, we performed in situ microscopic observation of Li deposition inside the SSE and obtained visualized evidence regarding the dynamic process of Li dendrite formation and growth. Li is seen to directly nucleate and propagate within the SSE, leading to its structural cracking. Such behavior should be caused by the presence of P- and S-based crystalline defects in Li3PS4 SSE, which is consistent with the cryo-transmission electron microscopy observations and theoretical calculations. This observation provides important insights into the growth mechanisms of Li dendrites within a working lithium battery.